Edukasi Antropometri pada Ibu Hamil Sebagai Upaya Prevensi Stunting di Dayeuh Kolot, Jawa Barat - Liana Nafisa Saftari; Dita Puspitasari; Fathur Rahman (Jurnal Abdimas Kesehatan (JAK), 2026)
Stunting is a chronic nutritional issue that hampers children's growth, characterized by height below the standard set by the World Health Organization (WHO). The primary cause is prolonged malnutrition, especially during the first 1,000 days of life—from pregnancy until the child turns two. In Indonesia, stunting has become a national priority due to its long-term impact on human resource quality and the country’s future. According to the 2022 Indonesian Nutrition Status Survey (SSGI), national stunting prevalence stands at 21.6%, while West Java reports 20.2%. In Bandung Regency, including Dayeuhkolot area, stunted children are still found, often due to inadequate monitoring during pregnancy and low maternal awareness about nutritional health. Efforts to reduce stunting should not focus only on toddlers but also prioritize early prevention during pregnancy. Maternal health—encompassing nutritional status, blood pressure, weight, and mid-upper arm circumference (MUAC)—plays a crucial role in determining the risk of delivering low birth weight (LBW) babies, a major stunting risk factor. However, many pregnant women lack knowledge of how to use basic health measurement tools like MUAC tapes, weight scales, and blood pressure monitors. Through this community service program, the team will conduct health education and practical training sessions for pregnant women at Posyandu 08 Melati, Citeureup Village, Dayeuhkolot. The initiative aims to improve maternal health literacy, equip participants with skills to use health tools, and raise early detection awareness for stunting prevention. A participatory, community-based approach will be applied to ensure sustainable impact in line with the government’s national stunting reduction agenda.